Wanprestasi Perjanjian Kerja Pegawai Perkebunan Karet di Desa Kalipapan: Tanggung Jawab dan Penyelesaian Hukum Perdata - Anita Anita; Ani Mardiantari (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to examine the practice of breach of employment agreements among rubber plantation workers, the resulting legal liability, and dispute resolution mechanisms from the perspective of Indonesian civil law. The research employed an empirical juridical method with a qualitative approach through fieldwork conducted in Kalipapan Village, Way Kanan Regency. Primary data were collected through observations and in-depth interviews with plantation owners, workers, and village officials, while secondary data were obtained from the Indonesian Civil Code, relevant statutory regulations, and scholarly literature. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing, with credibility ensured through source and technique triangulation. The findings reveal that breaches of employment agreements primarily occur in the form of failure to perform contractual obligations, delays in fulfilling work commitments, and violations of mutually agreed contractual terms. These breaches give rise to legal liability, including the obligation to perform the agreed obligations or compensate for losses in accordance with Indonesian civil law. Although disputes are predominantly resolved through community-based deliberation and consensual settlement, such mechanisms have not fully ensured legal certainty, highlighting the need to strengthen employment contracts and improve legal literacy among the contracting parties.